Famine exposure in early life increases risk of cataracts in elderly stage - Feng, Jiayuan; Niu, Hui; Zhu, Sijing; Xiang, Wanwan; Li, Xiaoxue; Deng, Yang; Xu, Xu; Yang, Wenfang; Chung, Mei Chun (Frontiers in Nutrition, 2024)
Background: Epidemiological studies have shown that early-life nutritional deficiencies are associated with an increased risk of diseases later in life. This study aimed to explore the correlation between famine exposure during the early stages of life and cataracts.We included 5931 participants from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) 2018 cross-sectional data in our study. Subjects were categorized into three groups by their age during the famine: adulthood group, school age famine exposure group, and teenage famine exposure group. Utilizing binary logistic regression models, we investigated the relationship between early-life famine exposure and cataracts.Results: Compared to the adulthood group, both the school age exposure group (OR=2.34,95%CI= 1.79-3.07) and teenage exposure group (OR=1.41,95%CI= 1.16-1.70) had a heightened risk of developing cataracts in elderly stage. And the sex differences in the impact of famine during early years on elderly cataract risk were observed, particularly indicating a higher risk among women who experienced childhood famine compared to men with similar exposure. Conclusions: Famine exposure during the early stages of life is associated with a heightened risk of developing cataracts in old age. To prevent cataracts in elderly individuals, particularly in females, measures should be taken to address nutritional deficiencies in these specific periods.